"I didn't know you were such a good cook": Photos as a tool for primary care clinician-patient communication. Issue 6 (June 2021) - Ho, Evelyn Y.; Leung, Genevieve; Fung, Jennifer; Jih, Jane
Highlights: Photo-based communication in primary care can promote patient activation. Patients and clinicians both initiate photo-based communication. Photos encourage a holistic, lifeworld-based discussion of dietary decision-making. Photo-based communication leads to suggestions, goal-setting, and referrals. Abstract: Objectives: To examine audio-recorded primary care interactions with patient-initiated photo sharing around food and diet choices. Methods: Data were 13 audio recordings of primary care visits with English-, Chinese-, or Spanish-speaking patients 60+ with two or more chronic conditions. Patients and clinicians completed pre-intervention surveys and some training on photo-taking / photo-sharing discussion. Data were analyzed using discourse analysis. Results: Photo-based communication interactions lasted 3:34−28:37 min and averaged one-third of the visit. Clinicians and patients both initiated the photo-based talk and transition to other topics occurred smoothly. In eight of 13 interactions, the photo-based communication task was raised, but conversation did not occur at that moment. When discussed, the photos raised opportunities to talk about patient's decision-making which led to dietary suggestions including clinical nutrition suggestions and referrals to other specialty clinics. Conclusion: Photo-based communication in primary care can be used to promote patient activation and facilitate collaborative decision making that accounts for the patients' lived experiences and lifeworld. Practice implications: By setting the agenda early, clinicians or patients can designate the photo-sharing as a relevant part of the visit. Photos may be most relevant as part of the problem presentation, diagnosis, or treatment recommendation sections of the visit.